Design and implementation of a modern modulation technique for modular multilevel converters - Parapelly, Kishore; C., Mahalakshmi; Gopala, Venu Madhav (International Journal of Electrical and Computer Engineering (IJECE), 2025)
The phase opposition disposition (POD) modulation technique is a sophisticated control strategy employed in modular multilevel converters (MMCs) to achieve high-quality output waveforms with minimized harmonic distortion. POD modulation employs numerous triangular carrier signals, positioned such that carriers above the zero-reference point are in phase, while those below are 180 degrees out of phase. This unique arrangement reduces even-order harmonics and enhances the overall power quality. By comparing a common sinusoidal reference signal with these phase-opposed carriers, pulse width modulation (PWM) signals are generated to control the insertion and bypassing of sub modules within the MMC. The modular structure and balanced switching pattern of POD modulation ensure efficient thermal management and reduced electrical stress on the components, significantly improving the reliability and lifespan of the converter. The technique’s inherent scalability and flexibility make it particularly suitable for renewable energy integration, HVDC systems, and industrial motor drives. This paper explores the principles, implementation, and advantages of the POD modulation technique in enhancing the performance and efficiency of MMCs in modern power electronics.